Redescription of Hypsibius microps Thulin, 1928 and H. pallidus Thulin, 1911 (Eutardigrada: Hypsibiidae) based on the type material from the Thulin collection - Kaczmarek, Łukasz; Michalczyk, Łukasz (Zootaxa, 2009)
Two species of the genus Hypsibius, H. microps and H. pallidus, are redescribed based on the type material from the Thulin collection. Those two species are very similar to each other and in the past their identification was based mostly on external claw morphology (identifications were very often doubtful and subjective). In this study we describe further differences between these two species. Apart from the claw morphology, H. pallidus differs from H. microps by: a larger body size, a wider buccal tube, longer placoids and placoid row and a longer pharynx. These two species differ also from other species attributed to the dujardini group by having granular rather than rod-shaped macroplacoids and by the absence of a constriction in the first macroplacoid.